2019
DOI: 10.3390/s19030444
|View full text |Cite
|
Sign up to set email alerts
|

Contactless In Situ Electrical Characterization Method of Printed Electronic Devices with Terahertz Spectroscopy

Abstract: Printed electronic devices are attracting significant interest due to their versatility and low cost; however, quality control during manufacturing is a significant challenge, preventing the widespread adoption of this promising technology. We show that terahertz (THz) radiation can be used for the in situ inspection of printed electronic devices, as confirmed through a comparison with conventional electrical conductivity methods. Our in situ method consists of printing a simple test pattern exhibiting a disti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…This model has been adapted for the determination of carrier lifetime and mobility in solar cell materials, , as well as the elucidation of charge injection and hopping processes in conjugated polymers . In situ studies of printed electronic devices by pump–probe THz spectroscopy have shown to produce reliable surface conductivity mapping in comparison to conventional methods such as AFM and four-point probe techniques . The absorption of the THz beam by the electrolyte and cell material is the biggest obstacle to the operando THz application in the presence of liquid electrolyte.…”
Section: Optical Spectroelectrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…This model has been adapted for the determination of carrier lifetime and mobility in solar cell materials, , as well as the elucidation of charge injection and hopping processes in conjugated polymers . In situ studies of printed electronic devices by pump–probe THz spectroscopy have shown to produce reliable surface conductivity mapping in comparison to conventional methods such as AFM and four-point probe techniques . The absorption of the THz beam by the electrolyte and cell material is the biggest obstacle to the operando THz application in the presence of liquid electrolyte.…”
Section: Optical Spectroelectrochemistrymentioning
confidence: 99%
“…231 In situ studies of printed electronic devices by pump−probe THz spectroscopy have shown to produce reliable surface conductivity mapping in comparison to conventional methods such as AFM and four-point probe techniques. 232 The absorption of the THz beam by the electrolyte and cell material is the biggest obstacle to the operando THz application in the presence of liquid electrolyte. Currently, operando implementation of THz spectroscopy for OMIECs is practically achievable using a THz transparent electrochemical cell.…”
Section: Ir and Thz Absorptionmentioning
confidence: 99%
“…To control the quality of conductive PE layers, Zhuldybina et al [83,114] iintroduced a simple strategy using a THz resonant structure as a quality control bar (QCB) for printing and characterized it by THz time-domain spectroscopy (THz-TDS). The main part of the THz-TDS system is a femtosecond (fs) laser, which, through an emitter, transforms the fs pulse into a picosecond THz pulse [115].…”
Section: Terahertz Time-domain Spectroscopy (Thz-tds)mentioning
confidence: 99%
“…Over the last 20 years, terahertz (THz) technology has witnessed great advances and development, opening the window to a wide range of new applications, such as imaging, non-destructive testing, telecommunication and even biologic applications [1][2][3][4][5]. These applications require powerful THz sources with high signal-to-noise ratios.…”
Section: Introductionmentioning
confidence: 99%